2013
DOI: 10.1016/j.vaccine.2013.06.084
|View full text |Cite
|
Sign up to set email alerts
|

Intussusception incidence among infants in the UK and Republic of Ireland: A pre-rotavirus vaccine prospective surveillance study

Abstract: HighlightsThe pre-rotavirus vaccine incidence of intussusception among UK and Irish infants was 24.8 and 24.2/100,000 live births.The highest incidence (50.3/100,000 live births) occurred in the fifth month of life (for England).A seasonal trend in intussusception was observed with the incidence significantly increased during winter and spring.Baseline rates will inform rotavirus vaccine-safety policy by enabling comparison with post-introduction incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 40 publications
10
25
0
Order By: Relevance
“…The higher rate in NL could be due to chance in this small provincial sample, differences in coding and reporting practices in NL, or genuinely higher incidence. Regional variation has been observed in other countries 17 . Further study including primary data collection would be necessary to verify and confirm the reasons for these higher rates.…”
Section: Discussionmentioning
confidence: 91%
“…The higher rate in NL could be due to chance in this small provincial sample, differences in coding and reporting practices in NL, or genuinely higher incidence. Regional variation has been observed in other countries 17 . Further study including primary data collection would be necessary to verify and confirm the reasons for these higher rates.…”
Section: Discussionmentioning
confidence: 91%
“…However, the epidemiological data on the risk of IS is limited in Asian countries where RV vaccination is expected to be introduced soon . In base line studies conducted in Europe and America, IS cases reported are less than 60 per 100 000 as compared with higher rates in Oceania including far east where >60 to 302/100 000 cases are reported and lower rates (<30/100 000) in Southeast and Central Asian countries …”
Section: Strategies To Control Rv Infectionmentioning
confidence: 99%
“…12.6 | RV vaccine and IS However, the epidemiological data on the risk of IS is limited in Asian countries where RV vaccination is expected to be introduced soon 143. In base line studies conducted in Europe and America, IS cases reported are less than 60 per 100 000 as compared with higher rates in Oceania including far east where >60 to 302/100 000 cases are reported and lower rates (<30/100 000) in Southeast and Central Asian countries 144. After introduction of rhesus reassortant tetravalent vaccineRotashield (RRV-TV; Wyeth Vaccines) in United States in the late 19th century, almost 30-fold risk of IS was observed 145,146.…”
mentioning
confidence: 99%
“…It is important to examine hernial orifices for signs of an incarcerated inguinal hernia and to consider volvulus secondary to malrotation, but the most common cause of intestinal obstruction in infants aged 3 months to 6 years is intussusception. The incidence of intussusception in the United Kingdom is 24.8/100 000 live births, 3 and the peak age of presentation is 4-7 months, although it can occur outside this age range. 4 The classic triad of redcurrant jelly stool, abdominal pain, and vomiting are the most familiar presenting symptoms of intussusception quoted by medical students.…”
Section: Long Answermentioning
confidence: 99%